Evaluating the Brand Gestalt of Emerging Health Tourism Destinations - Tappy, Yunita Peggy; Mandagi, Deske W. (Jurnal Studi Perhotelan dan Pariwisata, 2024)
Purpose: The aim of this study is to assess the brand gestalt of health tourism destinations (HTD) using the 4S brand gestalt dimension framework: storyscape, sensescape, servicescape, and stakeholderscape. D Method: ata were collected via a survey from 160 visitors to Manado, an emerging health tourism destination in North Sulawesi, Indonesia, specifically those visiting for health or medical treatment. Structural equation modeling (SEM) with SmartPLS software was employed for analysis. Result: The results indicate that all four dimensions significantly contribute to shaping the brand gestalt of HTD, with stakeholderscape emerging as the strongest predictor, followed by sensescape. These findings offer valuable insights for policymakers and Destination Management Organizations (DMOs), underscoring the need to enhance sensescape and servicescape elements to bolster the overall brand gestalt and attractiveness of health tourism destinations.